Anti-TNF antibody-induced psoriasiform skin lesions in patients with inflammatory bowel disease are characterised by interferon-γ-expressing Th1 cells and IL-17A/IL-22-expressing Th17 cells and respond to anti-IL-12/IL-23 antibody treatment. Issue 4 (6th March 2013) - Tillack, Cornelia; Ehmann, Laura Maximiliane; Friedrich, Matthias; Laubender, Rüdiger P; Papay, Pavol; Vogelsang, Harald; Stallhofer, Johannes; Beigel, Florian; Bedynek, Andrea; Wetzke, Martin; Maier, Harald; Koburger, Maria; et al.
Abstract : Background: We analysed incidence, predictors, histological features and specific treatment options of anti-tumour necrosis factor α (TNF-α) antibody-induced psoriasiform skin lesions in patients with inflammatory bowel diseases (IBD). Design: Patients with IBD were prospectively screened for anti-TNF-induced psoriasiform skin lesions. Patients were genotyped for IL23R and IL12B variants. Skin lesions were examined for infiltrating Th1 and Th17 cells. Patients with severe lesions were treated with the anti-interleukin (IL)-12/IL-23 p40 antibody ustekinumab. Results: Among 434 anti-TNF-treated patients with IBD, 21 (4.8%) developed psoriasiform skin lesions. Multiple logistic regression revealed smoking (p=0.007; OR 4.24, 95% CI 1.55 to 13.60) and an increased body mass index (p=0.029; OR 1.12, 95% CI 1.01 to 1.24) as main predictors for these lesions. Nine patients with Crohn's disease and with severe psoriasiform lesions and/or anti-TNF antibody-induced alopecia were successfully treated with the anti-p40-IL-12/IL-23 antibody ustekinumab (response rate 100%). Skin lesions were histologically characterised by infiltrates of IL-17A/IL-22-secreting T helper 17 (Th17) cells and interferon (IFN)-γ-secreting Th1 cells and IFN-α-expressing cells. IL-17A expression was significantly stronger in patients requiring ustekinumab than in patients responding to topical therapy (p=0.001). IL23R genotyping suggests disease-modifying effects of rs11209026 (p.Arg381Gln) and rs7530511 (p.Leu310Pro) in patients requiring ustekinumab. Conclusions: New onset psoriasiform skin lesions develop in nearly 5% of anti-TNF-treated patients with IBD. We identified smoking as a main risk factor for developing these lesions. Anti-TNF-induced psoriasiform skin lesions are characterised by Th17 and Th1 cell infiltrates. The number of IL-17A-expressing T cells correlates with the severity of skin lesions. Anti-IL-12/IL-23 antibody therapy is a highly effective therapy for these lesions.